Pollinator dependence of Argentinean agriculture: current status and temporal analysis. - Chacoff, Natacha P. (2010)
Fil: Chacoff, Natacha P. Instituto Argentino de Investigaciones de las Zonas Áridas (IADIZA)-CONICET; Argentina.